Effects of Substance Misuse and Family History of Substance Use Disorder on Delay Discounting in Adolescents and Young Adults with Attention-Deficit/Hyperactivity Disorder - Paraskevopoulou, Maria (Eur Addict Res, 2020)
BACKGROUND: Attention-deficit/hyperactivity disorder (ADHD) and substance use disorder (SUD) often co-occur. Both disorders are characterized by impulsive choice. However, little is known about the effects of substance misuse (SM) and family history of SUD (FH) on impulsive choice in ADHD-SUD comorbidity. Impulsive choice is also linked to callous-unemotional (CU) traits, which are suggested to play a role in ADHD-SUD comorbidity. Our aim was to examine the effects of (1) FH and (2) SM on impulsive choice, while exploring the role of CU traits. METHODS: Impulsive choice was assessed with the delay discounting (DD) task. We compared task performance across (1) ADHD patients and controls with or without FH of SUD (ADHD FH+: n = 86; ADHD FH−: n = 63; control FH+: n = 49; control FH−: n = 72; mean age of the whole sample [n = 270]: 16.39, SD: 3.43) and (2) family history-matched ADHD groups with and without SM and controls (ADHD + SM: n = 62; ADHD-only: n = 62; controls: n = 62; mean age of the whole sample [n = 186]: 18.01, SD: 2.71). Effects of CU traits were explored by adding this as a covariate in all analyses. RESULTS: (1) There was no main effect of FH on DD. (2) We found increased DD in ADHD + SM compared to ADHD-only and no difference between ADHD-only and controls. Finally, increased DD was associated with increased callous traits only in ADHD FH+ and control FH+. CONCLUSIONS: In adolescents and young adults with ADHD, high impulsive choice might only be present in those with comorbid SM and in an FH+ subgroup with high callous traits. This suggests that impulsive choice in ADHD might result from (1) effects of SM and (2) a combined effect of SUD vulnerability and high callousness. Future studies should investigate efficacy of early interventions, targeting CU traits.